An ever closer union among the peoples of Europe? Rising inequalities in the EU and their social, economic and political impacts: outcomes of EU–funded research - Jutta Allmendinger (An ever closer union among the peoples of Europe? Rising inequalities in the EU and their social, economic and political impacts: outcomes of EU–funded research, 2015)
– The European Treaty is based on an `ever closer union among the peoples of Europe'. Scientific research in social sciences and the humanities funded by the European Commission under the seventh framework programme shows that socioeconomic inequalities have generally increased in the EU over the last 20 years. A dual trend in inequalities has been observed during periods of economic growth as well as since the onset of the financial and economic crisis in 2008. First, inequalities reinforce the exclusion of already fragile citizens, trapping them into lives of exclusion from an early age. This issue triggers many questions as to what models of economic policy the EU should adopt and how these models should be combined with stronger social policies in favour of inclusion and solidarity. Second, rising inequalities threaten the quality of our democracies in Europe. Democracies thrive on equal treatment, proper regard to merit and opportunities for the excluded and the poor to live better lives. To ensure these rights, the EU needs to develop and implement targeted public policies in areas such as education and employment. This publication is aimed at supporting the agenda for jobs, fairness and democratic change put forward by Jean-Claude Juncker and the newly appointed European Commission.
Keywords: 330; aid to disadvantaged groups; equal treatment; EU Member State; poverty; quality of life; social inequality; social policy; socially disadvantaged class; socioeconomic conditions